Cash Expenditure Accounting Information System at PT PP Presisi Tbk Inkis Sumatra Toll Project - Alif Lailasari Saragih; Rahmat Daim Harahap (Penerbit Jurnal Indonesia, 2022)
Every activity requires funds in the form of cash. Cash is important in every transaction. This study aims to find out how the cash disbursements accounting information system is currently running at PT PP Presisi Tbk Inkis Sumatra Toll Project to find out whether the cash disbursement information system has been running effectively. The research method used in this paper uses qualitative methods, data collection techniques used are observation, interviews, and documentation. The data analysis method used is descriptive method. The results showed that the cash disbursement accounting information system at PT PP Presisi Tbk - Inkis Sumatra Toll Project was adequate because it was appropriate and fulfilled the basic elements of the accounting information system. running effectively..